UJI ATRAKTAN EKSTRAK KULIT BUAH KAKAO TERHADAP HAMA HELOPELTIS SP (HEMIPTERA : MIRIDAE) PADA KAKAO (Theobroma cacao L). - Sri Wahyuni; Lusia Fransiska Bhoko (AGRICA, 2021)
This study aims to determine the population, intensity of attack, Helopeltis spp and population relationship with damage to cocoa plants due to Helopeltis spp attack. This research was conducted in one location, namely in Embu Ndoa Village, Ende District, Ende Regency, with the condition that those who have not done P3S have yet. This study was conducted from January to March 2020. The variables observed were population and intensity of attack by Helopeltis spp. The results showed that the population of Helopeltis spp on cocoa plants at P1, P2, P3, respectively were 57, 24, 16 individuals/plant. The highest population of Helopeltis spp on cocoa was 57 individuals. The intensity of attack by Helopeltis spp was the highest at P1 was 54% with the highest R value of 0.2%.